Deglacial grounding-line retreat in the Ross Embayment, Antarctica, controlled by ocean and atmosphere forcing - Lowry, Daniel P.; Golledge, Nicholas R.; Bertler, Nancy A. N.; Jones, R. Selwyn; McKay, Robert (Science advances, 2019)
Oceanic and atmospheric warming were dominant controls of past ice sheet retreat in Antarctica’s largest catchment. Modern observations appear to link warming oceanic conditions with Antarctic ice sheet grounding-line retreat. Yet, interpretations of past ice sheet retreat over the last deglaciation in the Ross Embayment, Antarctica’s largest catchment, differ considerably and imply either extremely high or very low sensitivity to environmental forcing. To investigate this, we perform regional ice sheet simulations using a wide range of atmosphere and ocean forcings. Constrained by marine and terrestrial geological data, these models predict earliest retreat in the central embayment and rapid terrestrial ice sheet thinning during the Early Holocene. We find that atmospheric conditions early in the deglacial period can enhance or diminish ice sheet sensitivity to rising ocean temperatures, thereby controlling the initial timing and spatial pattern of grounding-line retreat. Through the Holocene, however, grounding-line position is much more sensitive to subshelf melt rates, implicating ocean thermal forcing as the key driver of past ice sheet retreat.